2020
DOI: 10.1186/s12889-020-09875-z
|View full text |Cite
|
Sign up to set email alerts
|

A rapid review of mental and physical health effects of working at home: how do we optimise health?

Abstract: Background The coronavirus (COVID-19) pandemic has resulted in changes to the working arrangements of millions of employees who are now based at home and may continue to work at home, in some capacity, for the foreseeable future. Decisions on how to promote employees’ health whilst working at home (WAH) need to be based on the best available evidence to optimise worker outcomes. The aim of this rapid review was to review the impact of WAH on individual workers’ mental and physical health, and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
327
1
17

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 361 publications
(420 citation statements)
references
References 42 publications
16
327
1
17
Order By: Relevance
“…Women still play a different social role as regards family and work [52]. A recent literature review on remote working due to the pandemic conducted by Oakman et al found that working at home reduced the opportunities for women to improve their health and was associated with poorer self-perceived health [53]. Besides, Chai et al described that non-spousal social support was more important for women's than men's health protection [54].…”
Section: Discussionmentioning
confidence: 99%
“…Women still play a different social role as regards family and work [52]. A recent literature review on remote working due to the pandemic conducted by Oakman et al found that working at home reduced the opportunities for women to improve their health and was associated with poorer self-perceived health [53]. Besides, Chai et al described that non-spousal social support was more important for women's than men's health protection [54].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence of the effects of working at home on physical and mental health are mixed. There is research to suggest that working at home can cause musculoskeletal issues increase stress and exhaustion but it can also improve wellbeing (see Oakman et al, 2020 )., The context to working at home is crucial in determining positive outcomes for individuals, including other demands of person around the home environment, the level of support from the employer and external social connections ( Oakman et al, 2020 ).…”
Section: Working From Homementioning
confidence: 99%
“…perpetuity. preprint (which was not certified by peer review) is the author/funder, who has granted medRxiv a license to display the preprint in The copyright holder for this this version posted March 26, 2021. ; https://doi.org/10.1101/2021.03.23.21254207 doi: medRxiv preprint There is currently no consistent evidence on the impact of working from home on the health and productivity of workers, as it varies depending on the worker's situation (20). While working from home has its advantages, including improved work-life balance and reduced burden of commuting, it also has disadvantages, including the psychological burden of a lack of separation between living and working spaces and time, and the lack of communication with colleagues.…”
Section: Discussionmentioning
confidence: 99%
“…There is currently no consistent evidence on the impact of working from home on the health and productivity of workers, as it varies depending on the worker’s situation (20). While working from home has its advantages, including improved work-life balance and reduced burden of commuting, it also has disadvantages, including the psychological burden of a lack of separation between living and working spaces and time, and the lack of communication with colleagues.…”
Section: Discussionmentioning
confidence: 99%